2012
DOI: 10.1007/s13181-012-0219-1
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium Phosphide Poisoning and Oxidative Stress

Abstract: According to previous animal studies, aluminium phosphides (AlPs) may induce oxidative stress leading to generation of free radicals and alteration in antioxidant defense system. This study was conducted to evaluate the existence and degree of oxidative stress in patients with acute AlP ingestion. A total of 44 acute AlP ingested patients as well as 44 age-and sex-matched controls were included. All patients had acute poisoning symptoms with AlP at the time of presentation and had blood samples analyzed for li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 21 publications
5
39
0
Order By: Relevance
“…Oxidative degradation of lipids known as lipid peroxidation, and other oxidant mechanisms damage biological macromolecules specially the cell membrane ultimately leading to cell death [29]. This is in agreement with our findings of significant increase in TBARS levels of plasma, liver and kidney of aluminium phosphide treated rats ( Table 1).…”
Section: Discussionsupporting
confidence: 92%
“…Oxidative degradation of lipids known as lipid peroxidation, and other oxidant mechanisms damage biological macromolecules specially the cell membrane ultimately leading to cell death [29]. This is in agreement with our findings of significant increase in TBARS levels of plasma, liver and kidney of aluminium phosphide treated rats ( Table 1).…”
Section: Discussionsupporting
confidence: 92%
“…In a previous study, AlP caused huge alterations in the levels of antioxidant enzymes . In other studies, severe reduction in antioxidant capacity was observed . A significant decrease was also shown in thiol group levels .…”
Section: Oxidative Stress: Effect Of Melatonin and Aluminium Phosphidementioning
confidence: 57%
“…The inhibition of respiratory chain complexes by AlP seems to initiate disastrous events resulting in ROS production. Consequently, these free radicals induce lipid peroxidation and DNA damage ending in blemished cycle which eventually leads to more oxidative stress and triggers apoptosis cascade in the cardiomyocytes . In a previous study, AlP caused huge alterations in the levels of antioxidant enzymes .…”
Section: Oxidative Stress: Effect Of Melatonin and Aluminium Phosphidementioning
confidence: 94%
See 1 more Smart Citation
“…Morever, Kariman et al (2012) (30) found that plasma total thiol concentration was lower in patients with acute aluminium phosphide toxicity versus control subjects, while the level of thiobarbituric reactive substance values showed a significant increase in patients compared with healthy controls.…”
Section: Discussionmentioning
confidence: 98%